Chemical composition and anti-microbial potential of essential oils from morphologically distinct Salvia rosmarinus (Spenn.) cultivars from Kashmir, India - Khan, Nafeesa Farooq; Bashir, Abid; Ganaie, Khursheed Ahmad; Shah, Sumaya Quadir; Nazir, Romaan; Sultan, Phalisteen; Hassan, Qazi Parvaiz (Frontiers in Microbiology, 2025)
IntroductionThe Kashmir Himalaya, renowned for its rich floristic diversity, harbors a multitude of native and introduced aromatic and medicinal plants. Among these, Salvia rosmarinus (rosemary), a Mediterranean native plant species, known for its culinary and therapeutic properties, is widely being cultivated owing to its local adaptability. Salvia rosmarinus essential oil has been used in folk medicine, pharmaceutical, and cosmetic industries. In our study, we compiled the morphological and chemoprofiling differences of field grown cultivars, wherein populations were grouped into 21 classes. Further, oils from identified accessions were screened for their anti-microbial potential against panel of four priority pathogens.Methods and resultsThe characterization was based on phenotypic traits (flower color variability, calyx color, flower size, and leaf morphology) variance across identified genotypes was validated using Chi 2 test. Abundance distribution data displayed polymorphism in evaluated character/traits of rosemary accessions and a total of 21 classes were reported from an underrepresented region. Furthermore, field grown Salvia rosmarinus cultivars in Kashmir Himalaya produced essential oil yield ranging from 0.8% to 1.7% maintaining benchmark constituents. Similarly, variability in chemical constituents using Gas Chromatography Mass Spectrometry (GC/MS), grouped accessions into chemotypes rich in beta-myrcene, 1,8 cineole, and camphor. Antimicrobial assays on the essential oils obtained from different accessions using gram-negative and gram-positive bacteria and one fungal pathogen were conducted to directly evaluate the IC50 (concentration at which there is 50 percent growth inhibition of pathogen) and Minimum Inhibitory concentration (MIC) values. MIC evaluation of the active essential oil was performed using the broth dilution method.DiscussionThe data generated in this study emphasizes the use of morphological and chemical characteristics to characterize and conserve elite Salvia rosmarinus cultivars, promoting cultivar R1 (1.7%) in summer season and R14 (0.95%) and R3 (0.93%) in winter season for large-scale cultivation, emphasizing propagation of higher essential oil yielding varieties in Kashmir Himalaya. The diverse rosemary genepool conserved in Kashmir exhibits significant variability in essential oil yield and composition while, certain accessions demonstrate potent antimicrobial properties. The findings of the study are useful for further elaborate studies on the development of natural bioactive compounds to improve human health.